Laryngo-tracheo-bronchial foreign bodies: epidemiological, diagnostic and therapeutic aspects - Amana, Bathokédéou; Pegbessou, Essobozou Plaodezina; Amana, Essobiziou; Foma, Winga; Dolou, Warou; Laws, Stephen; Boko, Essohanam; Kpemissi, Eyawelohn (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to describe the epidemiological, diagnostic and therapeutic aspects of laryngo-tracheo-bronchial (LTB) foreign bodies (FB). Methods: A 20-year retrospective study, performed in the ENT, head and neck surgery department of Sylvanus Olympio Teaching Hospital in Lomé, dealing with patients treated for this LTB. Results: Sixty-one cases of LTB FB were collected. The LTB FB represented 3.05 cases per year, 11.71% of the FB airways and 4.08% of ENT FB. Thirty-two patients (52.46%) were male, a sex ratio of 1.10. The average age of patients was 5.08 years, with extremes of 4 months and 43 years. In 31 cases (50.82%), the accident occurred during the meal and in 30 cases (49.18%) during a game. The penetration syndrome was found in 54 cases (88.52%). FB was extracted by rigid tube bronchoscopy in 50 patients (81.97%). The most common site of endoscopy was right bronchus in 30 cases (49.18%) and in 11 cases (18.03%) FB was laryngeal. Organic FB accounted for 31 cases (50.82%) and was dominated by peanuts (29.5%), for non-organic FB they were dominated by pebbles (8.2%). The evolution was favorable in 58 cases (95.08%). Conclusions: Severe accidental pathology, the prognosis depends on the nature of the body, its seat and the time of care.